Determinants of pro-environmental behavior among excessive smartphone usage children and moderate smartphone usage children in Taiwan - Wei-Ta Fang; Eric Ng; Shu-Mei Liu; Yi-Te Chiang; Mei-Chuan Chang (PeerJ, 2021)
Introduction Although there is evidence linking the relationships between smartphone usage with health, stress, and academic performance, there is still inadequate knowledge about the influence on pro-environmental behaviors. This study seeks to bridge this gap by adapting the theory of attribution framework to examine the effects of personal norms, social norms, perceived behavioral control on pro-environmental behavior of smartphone usage in children. Methods A total of 225 children aged between 11 to 12 from eight selected public primary schools at the Hsinchu Science and Industrial Park in Taiwan were surveyed. Two distinct groups (excessive versus moderate usage) were purposefully selected for comparison, of which 96 participants were excessive smartphone users while the remaining 129 were moderate smartphone users. Results Findings revealed significant differences between excessive and moderate smartphone usage children groups in personal norms (p < 0.001), social norms (p = 0.002), perceived behavioral control (p = 0.001), and pro-environmental behavior (p = 0.001). Findings for excessive smartphone usage children showed that social norms (β = 0.428, t = 4.096***, p < 0.001) had a direct predictive impact on pro-environmental behavior. In contrast, while there was no direct path established between personal norms and pro-environmental behavior (β = 0.177, t = 1.580, p > 0.05), as well as social norms and pro-environmental behavior for moderate smartphone usage children (β = 0.181, t = 1.924, p > 0.05), but such a relationship could be developed through the mediating effect of perceived behavioral control (β = 0.497, t = 4.471***, p < 0.001). Discussion The results suggested that excessive smartphone usage children lack positive perceived behavioral control, and their pro-environmental behavior could only be predicted through explicit social norms, whereas pro-environmental behavior of moderate smartphone usage children was implicitly influenced by personal norms through perceived behavioral control.